Fairness preferences in a bilateral trade experiment - Alice Ciccone; Ole Rogeberg; Ragnhild Haugli Braaten (Games, 2020)
Is the willingness to make trades influenced by how the total gains from trade are split between the trading partners? We present results from a bilateral trade game (n = 128) where all participants were price-takers and trading pairs faced one of three exogenously imposed trading prices. The fixed prices divided the gains either symmetrically in the reference treatment or asymmetrically in treatments favoring either the buyer or seller. Price treatments generating asymmetric gains from trade reduced desired transaction levels on both sides of the market, but more strongly by the disfavored party. The data weakly indicated a larger reduction when the disfavored party was a seller.
Keywords: C90; D02; D03; D63; 330; experiment; fairness; inequality aversion; markets; social preferences; trade